2009
DOI: 10.1099/vir.0.009589-0
|View full text |Cite
|
Sign up to set email alerts
|

Orf virus-encoded chemokine-binding protein is a potent inhibitor of inflammatory monocyte recruitment in a mouse skin model

Abstract: The parapoxvirus orf virus causes pustular dermatitis in sheep and is transmissible to humans. The virus encodes a secreted chemokine-binding protein (CBP). We examined the ability of this protein to inhibit migration of murine monocytes in response to CC inflammatory chemokines, using chemotaxis assays, and its effects on monocyte recruitment into the skin, using a mouse model in which inflammation was induced with bacterial lipopolysaccharide. CBP was shown to bind murine chemokines CCL2, CCL3 and CCL5 with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 36 publications
4
41
1
Order By: Relevance
“…The chemokine-binding spectrum and affinities of the BPSV CBP were consistent with those reported for the CBP from its fellow parapoxvirus, orf virus. [13][14][15]18 After establishing the ability of the CBP to inhibit a broad spectrum of chemokines, we investigated its efficacy in vivo. We found that intravenous administration of the CBP after transient cerebral ischemia largely prevented stroke-induced increases in circulating levels of key chemokines in association with milder neurological deficit at 24 hours.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The chemokine-binding spectrum and affinities of the BPSV CBP were consistent with those reported for the CBP from its fellow parapoxvirus, orf virus. [13][14][15]18 After establishing the ability of the CBP to inhibit a broad spectrum of chemokines, we investigated its efficacy in vivo. We found that intravenous administration of the CBP after transient cerebral ischemia largely prevented stroke-induced increases in circulating levels of key chemokines in association with milder neurological deficit at 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…The CBP from orf virus, the type species of the parapoxvirus genus, binds a range of CC, CXC, and C chemokines with high affinity and can neutralize the activity of CC chemokines in vitro and in vivo. [13][14][15]18 Publication of the complete genome sequence of another parapoxvirus, BPSV strain AR-02 revealed an equivalent CBP ≈24 kb from the right terminus of the genome. 16 We therefore sequenced the corresponding region in the BamHI A fragment of the genome from BPSV strain V660 and identified an equivalent CBP.…”
Section: Cbp Binds a Broad Spectrum Of CC Cxc And C Chemokines Withmentioning
confidence: 99%
See 2 more Smart Citations
“…Myxoma viruses deficient in M-T1(vCCI) have a subtle phenotype, with an increase in leukocyte infiltration but no significant difference in disease progression or mortality (18,25). In addition, mouse studies of ORF virus infection, a zoonotic parapoxvirus, shown to encode vCCI-like chemokine binding protein (26), demonstrated that ORF virus (ORFV) vCCI blocks the recruitment of immature and mature dendritic cells to the skin and lymph nodes and inhibits T cell responsiveness in lymph nodes (26,27). The role of herpesvirusencoded chemokine binding proteins in pathogenesis and immune modulation remains poorly understood, in part due to lack of the appropriate experimental host.…”
mentioning
confidence: 99%